Design Considerations for Wind Turbine Systems - Simoes, M.; Muyeen, S.M.; Al-Durra, A. (CRC Press, 2017)
In this chapter, the fundamentals of wind energy conversion system including wind turbine components, drive train, wind turbine characteristics, and wind generators are explained at the beginning. Then the design considerations of a small wind turbine generator system such as wind speed probability distribution, component losses, system efficiency, etc., are explained in detail. Different types of wind turbine generator system topologies including fixed and variable speed systems are presented. Finally, mechanical, electrical, and overall control schemes of wind energy conversion system are demonstrated.